2007
DOI: 10.1371/journal.pgen.0030087
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Cartography of Estrogen Receptor α Binding Sites

Abstract: Using a chromatin immunoprecipitation-paired end diTag cloning and sequencing strategy, we mapped estrogen receptor α (ERα) binding sites in MCF-7 breast cancer cells. We identified 1,234 high confidence binding clusters of which 94% are projected to be bona fide ERα binding regions. Only 5% of the mapped estrogen receptor binding sites are located within 5 kb upstream of the transcriptional start sites of adjacent genes, regions containing the proximal promoters, whereas vast majority of the sites are mapped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
413
6
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(466 citation statements)
references
References 47 publications
42
413
6
1
Order By: Relevance
“…In general, it is not unusual for large introns, such as intron 2 of the PRKCB1 gene, which spans approximately 150 kb, to produce totally intronic noncoding RNAs, especially frequent among members of the Gene Ontology 'Regulation of transcription' gene category. 51 Alternatively, single base pair changes can indeed affect gene expression by creating or deleting an intronic response element, enhancer or repressor, 52 as recently demonstrated for a single base pair change causing the loss of an Sp1 response element in the MET gene promoter. 4 Regardless of the underlying mechanism, the association of PRKCB1 'risk' alleles with a blunted adaptive downregulation of gene expression seemingly fits with several converging lines of evidence.…”
Section: Discussionmentioning
confidence: 97%
“…In general, it is not unusual for large introns, such as intron 2 of the PRKCB1 gene, which spans approximately 150 kb, to produce totally intronic noncoding RNAs, especially frequent among members of the Gene Ontology 'Regulation of transcription' gene category. 51 Alternatively, single base pair changes can indeed affect gene expression by creating or deleting an intronic response element, enhancer or repressor, 52 as recently demonstrated for a single base pair change causing the loss of an Sp1 response element in the MET gene promoter. 4 Regardless of the underlying mechanism, the association of PRKCB1 'risk' alleles with a blunted adaptive downregulation of gene expression seemingly fits with several converging lines of evidence.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the binding motifs of transcription factors, including FOXA1, C/EBP, and Oct, have also shown to be positively correlated with ER [59] . Lin et al used ChIP-paired end diTag (ChIP-PET) technology and deep-sequencing for mapping ERBSs in the genome of MCF-7 cells [65] . In their report, 1234 high-confidence ERα-binding sites (ERBSs) were identified and several transcription factor binding motifs, including Sp1, AP-1, and FOXA1 were found to be enriched with the ERBSs.…”
Section: Identification Of Estrogen-responsive Genes Using Highthrougmentioning
confidence: 99%
“…Using GRO-seq analysis, Hah et al revealed that the expression of ~3000 protein-coding genes is regulated by estrogen in MCF-7 cells [83][84][85] . Combined GRO-seq and ChIP-seq analysis in MCF-7 cells has shown that half of the immediate early estrogenresponsive genes possesses ERBSs in the vicinity (10 kb) of the transcription start site, although other studies have shown that ERBSs are dispersed throughout the genome [59,65,66,69,83] .…”
Section: Identification Of Estrogen-responsive Genes Using Highthrougmentioning
confidence: 99%
“…We crossed several studies from the recent literature based on microarray transcriptome analyses and ChIP-chip, ChIP-DSL or ChIP-paired end di-tag data obtained from mammary tumor cell lines (Lin et al, 2004(Lin et al, , 2007Laganiere et al, 2005;Kininis et al, 2007;Kwon et al, 2007) to select a group of relevant genes based on the following criteria: hormone-stimulated gene expression in ERa-positive mammary tumor cell lines, complete lack of expression in ERa-negative breast cancer cell lines (Nagaraja et al, 2006) and ERa target identified by ChIP. Thus, we investigated gene regulation of Annexin A9 (ANXA9), a gene coding for a protein of the annexin superfamily (Raynal and Pollard, 1994;Gerke and Moss, 2002), the RET proto-oncogene, which encodes a protein receptor tyrosine kinase with a zinc finger domain associated with dominantly inherited cancer syndromes (Goodfellow and Wells, 1995), the tumor protein D52-like 1 (TPD52L1 (D53)) upregulated in human breast and prostate cancers (Balleine et al, 2000;Ahram et al, 2002;Pollack et al, 2002;Rubin et al, 2004), bone morphogenetic protein-6 (BMP6), a multifunctional molecule of the transforming growth factor-b superfamily overexpressed in breast, prostate and salivary gland cancers (Hamdy et al, 1997;Heikinheimo et al, 1999) and the gene regulated in breast cancer 1 (GREB1), whose product contributes to the growthpromoting effects of estrogens in MCF-7 cells (Rae et al, 2005).…”
Section: Dna Demethylation and Histone Deacetylation Trigger Hormone-mentioning
confidence: 99%